Mobile apps for ELLs: Supporting language learning with engaging digital tools - Alvarado, Nery Carmen; Coelho, Daniela; Dougherty, Ellen (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In our contemporary society, the ability to speak a foreign language is becoming more valued than ever before by prospective employers and, consequently, this ability offers greater opportunities and possibilities for students, both academically and professionally. Therefore, in response to this trend, language teachers are motivated to employ the most recent language teaching methodologies, resources and materials with their students, such as the use of ICT, Information and Communication Technologies, namely mobile learning, MALL. In this article, the authors will explore three mobile learning apps or digital tools that enhance language learning in engaging, interactive environments. The authors’ focus will be on showing samples of interactive activities developed in their classes, as well as on sharing exemplars of work done by students.